METAVERSE EXPERIENCE AS A MEDIATOR BETWEEN GAME-INDUCED TOURISM AND TOURIST MOTIVATION (Jurnal IPTA (Industri Perjalanan Wisata), 2026)
This research investigates how game-induced tourism shapes tourist motivation and explores the extent to which metaverse experience functions as an intermediary mechanism within a game-based virtual environment. Drawing on the Stimulus-Organism-Response (S-O-R) framework, game-induced tourism is conceptualized as the external stimulus, metaverse experience as the internal organism state, and tourist motivation as the resulting behavioral response. The study adopts a quantitative, cross-sectional design in which survey data were gathered from 380 participants who had previously engaged with destination-oriented content through the ROBLOX platform. Sampling was carried out using purposive criteria to ensure respondent eligibility, and data were subjected to analysis via Partial Least Squares Structural Equation Modeling (PLS-SEM) implemented in SmartPLS 3. Findings reveal that game-induced tourism had a positive influence on tourist motivation. Game-induced tourism further demonstrates a strong effect on metaverse experience, while metaverse experience in turn positively and significantly affects tourist motivation. Mediation analysis confirms that metaverse experience significantly mediated the relationship between game-induced tourism and tourist motivation. These findings contribute to the digital tourism and media-induced tourism literature while offering practical insights for destination marketing organizations leveraging game-based metaverse platforms.
Keywords: Game Induced Tourism; Metaverse Experience; ROBLOX; tourist motivation; virtual tourism